Corruption in Society: Multidisciplinary Conceptualizations - Gire, James T. (Lexington Books/Fortress Academic, 2023)
This book questions whether we really have a full enough understanding of corruption to craft holistic laws and policies to deal with it. The contributors provide a discipline-by-discipline conceptualization of corruption buttressed with evidence from the discipline to fill the gaps in the prevalent definition and understanding of corruption.